The Impact of Business Size, Human Resources, and Technology Use on The Quality of Financial Reports on Small and Medium Size Entities in The Tegal Regency - Ibnu Muttaqin (Accounthink : Journal of Accounting and Finance, 2022)
The purpose of the study was to analyze the size of the business, human resources and the use of technology on the quality of financial reports on MSMEs in Tegal Regency. This research method is a quantitative type with primary data using a questionnaire in data collection. The sample in this study is MSMEs in Tegal Regency. Sampling using purposive sampling technique is to determine the sample with certain considerations. The analytical tool used is using SPSS with multiple linear regression analysis. The results of the study partially show that the size of the business has no effect on the quality of financial reporting. Human resources have a significant effect on the quality of financial reports. The use of technology has a significant positive effect on the quality of financial reports. The results of the study simultaneously have a significant effect on the quality of financial reports in MSMEs in Tegal Regency. Keywords: Business size; Human Resources; Technology Utilization; Quality of financial reports.